Analisis Komparatif Faktor Penyebab Terjadinya Perceraian Di Negara-Negara Muslim - Wartono, Nanang; Akbarizan (Muhammadiyah University of Surabaya, 2025)
This study aims to analyze the factors causing divorce in various Islamic countries, considering social, cultural, economic, and Islamic legal aspects. The approach used is qualitative library research, where data is obtained from various scientific literature, reports from international institutions, and legal documents related to divorce in countries such as Indonesia, Pakistan, India, Egypt, Kuwait, Jordan, Qatar, Turkey, and Malaysia. The analysis is conducted using content analysis and comparative case studies to uncover the different patterns of divorce causes in each Muslim country. The results of this study indicate that the main causes of divorce in Muslim countries include persistent disorder and conflict, economic problems, domestic violence, infidelity, as well as the influence of social media and changing gender roles. In countries with traditional social systems such as Pakistan and Egypt, divorce is more often triggered by gender inequality and domestic violence, while in modern countries such as Turkey and Malaysia, divorce is influenced by individualism and the use of digital technology. Indonesia and India, on the other hand, exhibit a combination of traditional and modern factors. The implication of this research is that social policies and family education based on Islamic values ​​are needed that are contextual to modern social dynamics, including strengthening premarital education, family counseling, and ethical use of digital media to strengthen the resilience of Muslim families. Keywords: Divorce, Muslim Countries, Social Factors, Economy, Social Media, Gender.